Phomopsis longanae Chi-Induced Disease Development and Pericarp Browning of Harvested Longan Fruit in Association With Energy Metabolism - Chen, Yihui; Lin, Hetong; Zhang, Shen; Sun, Junzheng; Lin, Yifen; Wang, Hui; Lin, Mengshi; Shi, John (Frontiers in Microbiology, 2018)
Longan fruit is a popular subtropical fruit with a relatively short shelf life at room temperature mainly due to pericarp browning and fungal infection. This study aimed to investigate the infection of Phomopsis longanae Chi in longan fruit and its effects on the storability and shelf life of longan fruit. The relationship between the energy metabolism of harvested longan fruit and disease development and pericarp browning was elucidated. Results show that P. longanae-inoculation accelerated the deterioration of longan fruit and caused pericarp browning. It also led to the energy deficit in pericarp of longan fruit, which was reflected as lower contents of ATP and ADP, higher AMP content, and lower energy charge as compared to the control samples. Additionally, P. longanae-infection reduced the activities of H+-ATPase, Ca2+-ATPase, and Mg2+-ATPase in plasma, vacuolar, and mitochondrial membranes during the storage period. The results demonstrate that P. longanae-infection led to disease development and pericarp browning in harvested longan fruit, which were due to the infection-induced energy deficit and low ATPase activity that caused disorders of ion transport and distribution, and damaged the structure and function of vacuole, mitochondria, and eventually the whole cells of fruit tissues.